The Role of the Sidoarjo Helath Center in Stunting Prevention : Peran Puskesmas Sidoarjo dalam Penanggulangan Stunting - Luluk Herawati; Ilmi Usrotin Choiriyah (Academia Open, 2025)
General Background: Stunting remains a persistent global health issue with significant implications for human development, particularly in Indonesia, where it affects children’s physical and cognitive growth and threatens the nation’s demographic potential. Specific Background: The Sidoarjo Health Center (Puskesmas) operates as a primary healthcare facility and serves as a key institution in implementing the government’s national strategy for accelerating stunting reduction. Knowledge Gap: Despite numerous government initiatives, the specific mechanisms and effectiveness of local health centers in addressing stunting through community-based interventions remain underexplored. Aims: This study aims to analyze the role of the Sidoarjo Health Center in stunting prevention using Gayatri’s (2005) role theory, which categorizes institutional functions as motivator, facilitator, and dynamicator. Results: The findings reveal that Puskesmas Sidoarjo successfully fulfills these roles by motivating health workers and the community, providing adequate medical facilities, and fostering cross-sector collaboration with government, academia, and civil organizations. Novelty: The study offers a localized perspective on stunting prevention, highlighting the integration of community empowerment and inter-sectoral partnerships at the primary healthcare level. Implications: Strengthening Puskesmas as a dynamic health actor can enhance national stunting reduction programs, ensuring sustainable improvements in child health and nutrition outcomes.Highlight : The Sidoarjo Health Center acts as a motivator in providing nutrition education and stunting prevention for the community. As a facilitator, the Health Center provides medical equipment to support stunting prevention programs. As a dynamicator, the Health Center establishes cross-sector collaboration to strengthen program implementation. Keywords : Role, Stunting Prevention, Sidoarjo Health Center, Motivator, Facilitator